Pattern Recognition, Tracking and Vertex Reconstruction in Particle Detectors - Frühwirth, Rudolf (2021)
The book describes methods of track and vertex resonstruction in particle detectors. The main topics are pattern recognition and statistical estimation of geometrical and physical properties of charged particles and of interaction and decay vertices.